Genetic Identification of Methicillin-Resistant Staphylococcus aureus Nasal Carriage and Its Antibiogram among Kidney Dialysis Patients at a Tertiary Care Hospital in AL-Karak, Jordan - Al-Dmour, Omar; Al-Groom, Rania; Alsheikh, Ayman; Mahmoud, Sameer; Amawi, Kawther; Yousef, Israa; Almaraira, Ayat (International Journal of Microbiology, 2023)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) is a major bacterial pathogen. Aim. The present study aimed to determine the incidence of MRSA infections among kidney dialysis patients and the antibiotic susceptibility patterns and investigate the prevalence of mecA gene among MRSA isolates. Materials and Methods. A total of 83 nasal sterile cotton swabs samples were obtained from hemodialysis patients from Al-Karak Governmental Hospital, Al-Karak, Jordan. Collected and cultured on nutrient agar and mannitol salt agar and incubating at 37°C for 24–48 hours, Staphylococcus aureus (S. aureus) strains were identified by gram stain, coagulase test, and catalase tests. The MRSA isolates were tested for the presence of MecA and SCCmec genes using the Xpert SA Nasal Complete assay real-time PCR. Factors such as age and gender were included in the study. The antibiotic profile tested by using the disc diffusion method tested all MRSA isolates. Results. This study showed that 10.8% of the cultures’ growth was S. aureus and 9.6% of all the patients were infected with MRSA, with no relationship between the number and frequency of MRSA according to the patient’s gender or age. All MRSA (100%) isolates have both genes (MecA genes and SCCmec genes), and all samples were resistant to oxacillin, ceftazidime, cefoxitin, aztreonam, and ampicillin. Conclusion. The MRSA prevalence was determined among kidney dialysis patients in the hospital. All positive samples were resistant to oxacillin, ceftazidime, cefoxitin, aztreonam, and ampicillin, which is a very rare finding, and this will give the scientists and doctors a dangerous indication about health-care centers in the Al-Karak city of Jordan.